FAKTOR-FAKTOR RESIKO STROKE ISKEMIK PADA PASIEN DI RUMAH SAKIT PTPN II BANGKATAN BINJAI TAHUN 2016 - Wahyuni, Sri (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Ischemic stroke is a stroke that is almost 25% caused by blockage of a blood clot, narrowing of an artery or some arteries that lead to the brain or embolus (feces) that is released from the heart or an estrhetic artery (an artery outside the skull) that causes a single or multiple arteries intracran (arteries inside the skull). The purpose of this study was to determine the risk factors for ischemic stroke in PT Departure II Bangkat Binjai Hospital. This type of research is descriptive with a cross sectional design. The population in this study were all ischemic stroke patients with a sample of 42 people. The results showed that the majority of patients aged 50-55 years as many as 15 people (36%), the majority of patients were male as many as 24 people (57%), the majority of patients had elementary education as many as 16 people (38%), the majority the work of patients is working as civil servants as many as 14 people (33%). Ischemic stroke due to hypertension as many as 32 people (76%), ischemic stroke due to smoking as many as 22 people (52%), ischemic stroke due to diabetes as many as 23 people (55%), ischemic stroke due to cholesterol as many as 21 people (50%). Ischemic stroke sufferers must know more about what is meant by prevention and treatment obtained from the medical team. It is expected that ischemic stroke patients will control things that affect or encourage ischemic stroke. It is expected that medical personnel can provide an explanation and counseling to ischemic stroke patients about ischemic stroke risk factors and their preventionKeywords: Risk Factors, Ischemic Stroke